The Prospect Theory and First Price Auctions: an Explanation of Overbidding - Josheski, Dushko; Apostolov, Mico (Teoria perspektywy i aukcje pierwszej ceny: wyjaśnienie przebijania, 2023)
This paper attempted using the prospect theory to explain overbidding in first price auctions. The standard outlook in the literature on auctions is that bidders overbid, but the probability weighting functions are nonlinear as in the prospect theory, so they not only tend to underweight the probabilities of winning the auction but also overweight, so that there are overbidders and underbidders. This paper proves that to some extent, non-linear weighting functions do explain overbidding the risk-neutral Nash equilibrium valuation (RNNE). Furthermore, coherent risk measures, such as certainty equivalent and translation invariance, were used to show loss aversion among bidders, and in line with the prospect theory, convexity was also confirmed with sub-additivity, monotonicity and with positive homogeneity.
Econometrics = Ekonometria, 2023, Vol. 27, No. 1, s. 33-74
Keywords: cumulative prospect theory; first-price auctions; overbidding; probability weighting function; inverse S-shaped functions; kumulatywna teoria perspektywy; aukcje pierwszej ceny; przelicytowanie; funkcja ważenia prawdopodobieństwa; odwrotne funkcje S-kształtne